The relationship between family support and religiosity with gamophobia in career women: A correlational study - Bonivia, Repika; Ahmad, Bukhari (Empathy : Jurnal Fakultas Psikologi, 2025)
Excessive fear of marital commitment, known as gamophobia, among adult career women has received limited scholarly attention, particularly within psychosocial and religiosity frameworks. This study investigated the effects of family support and religiosity on gamophobia among career women aged 33 years and older. A quantitative correlational approach was applied using multiple regression analysis. The study involved 47 career women recruited through purposive sampling. Data were gathered using standardized Likert type instruments and analyzed with SPSS version 26. The findings revealed that family support (β = –0.420, p < .001) and religiosity (β = –0.495, p < .001) were significant negative predictors of gamophobia, with the model explaining 52% of the variance (R² = 0.52). These results highlight the complementary roles of social support in fostering emotional regulation and religiosity in providing existential meaning, both of which contribute to reducing fear related to marital commitment. From a practical perspective, the findings suggest that intervention programs integrating family support enhancement and religiosity reinforcement may be effective in alleviating gamophobia among adult career women.